) Design and development of molecularly imprinted polymers for the selective extraction of deltamethrin in olive oil: an integrated computational-assisted approach - Martins, Nuno (2015)
tThis work firstly addresses the design and development of molecularly imprinted systems selective fordeltamethrin aiming to provide a suitable sorbent for solid phase (SPE) extraction that will be furtherused for the implementation of an analytical methodology for the trace analysis of the target pesticidein spiked olive oil samples. To achieve this goal, a preliminary evaluation of the molecular recogni-tion and selectivity of the molecularly imprinted polymers has been performed. In order to investigatethe complexity of the mechanistic basis for template selective recognition in these polymeric matri-ces, the use of a quantum chemical approach has been attempted providing new insights about themechanisms underlying template recognition, and in particular the crucial role of the crosslinker agentand the solvent used. Thus, DFT calculations corroborate the results obtained by experimental molecu-lar recognition assays enabling one to select the most suitable imprinting system for MISPE extractiontechnique which encompasses acrylamide as functional monomer and ethylene glycol dimethacrylateas crosslinker. Furthermore, an analytical methodology comprising a sample preparation step based onsolid phase extraction has been implemented using this “tailor made” imprinting system as sorbent, forthe selective isolation/pre-concentration of deltamethrin from olive oil samples. Molecularly imprintedsolid phase extraction (MISPE) methodology was successfully applied for the clean-up of spiked olive oilsamples, with recovery rates up to 94%.